2013
DOI: 10.1111/joa.12029
|View full text |Cite
|
Sign up to set email alerts
|

Development of epithelial and mesenchymal regionalization of the human fetal utero‐vaginal anlagen

Abstract: Literature on the development of the human vagina is abundant; however, contributions concerning the prenatal development of the entire utero-vaginal anlagen (UVA) are rare or carried out in rodents. The primary epithelial characteristics in the adult vagina and uterus are determined during prenatal development and depend on epithelio-mesenchymal stroma interaction; thus an investigation summarizing the spatiotemporal distribution of relevant molecular markers in the entire human UVA will be of current interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…With this caveat, we have re-visited the classic studies of Koff and Bulmer and extended the more recent studies of Fritsch et al by providing detailed high-resolution documentation of human female reproductive tract development (Bulmer, 1957; Fritsch et al, 2012; Fritsch et al, 2013; Koff, 1933). Significantly, through use of immunohistochemistry we have described the dynamic age-dependent changes in the contribution of Müllerian versus UGS epithelium in the development of human vaginal epithelium, which depart markedly from the complete elimination of UGS epithelial cells from vaginal epithelium in mice (Kurita, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…With this caveat, we have re-visited the classic studies of Koff and Bulmer and extended the more recent studies of Fritsch et al by providing detailed high-resolution documentation of human female reproductive tract development (Bulmer, 1957; Fritsch et al, 2012; Fritsch et al, 2013; Koff, 1933). Significantly, through use of immunohistochemistry we have described the dynamic age-dependent changes in the contribution of Müllerian versus UGS epithelium in the development of human vaginal epithelium, which depart markedly from the complete elimination of UGS epithelial cells from vaginal epithelium in mice (Kurita, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Various theories have suggested that vaginal epithelium receives contributions from epithelium of the urogenital sinus, Müllerian or Wolffian ducts alone or in combination (Koff, 1933; O’Rahilly, 1977; Forsberg, 1978; Bulmer, 1957). Particularly valuable are the recently published works of Cai and Fritsch et al (Cai, 2009; Fritsch et al, 2012; Fritsch et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations